Energy-efficient clustering protocol for underwater wireless sensor networks using optimized glowworm swarm optimization - Salil Bharany; Sandeep Sharma; Naif Alsharabi; Elsayed Tag Eldin; Nivin A. Ghamry (Frontiers in Marine Science, 2023)
In the past few decades, cutting-edge information and communication technology has been used in several ways to keep an eye on the marine environment. Underwater wireless sensor networks (UWSNs) can measure the amount of water and soil conditions, such as soil salinity, moisture, and movements, to predict landslides. UWSNs are made up of many wireless underwater sensor nodes (WSNs) that are spread out across the thalassic environment. These networks have several uses, including data collection, navigation, resource analysis, surveillance, disaster prediction, etc. Nowadays, energy efficiency becomes a complex issue to handle in the design of the UWSN due to the limited battery capacity and the challenges associated with changing or charging the integrated batteries. According to previous research, clustering and routing have already been effective methods of improving energy efficiency in the UWSN, as unreplaceable batteries and long-distance communication delays are particularly vulnerable. As a result, one of the UWSN’s critical issues is determining how to extend the network’s lifespan while balancing its energy consumption and shortening transmission distances. In UWSN clustering, the most important considerations are acquiring a suitable count of clusters, constituting the clusters, and picking the most satisfactory cluster head (CH) for each cluster. Based on several factors, such as residuary energy, total energy consumption, and other considerations, our proposed approach picks CHs and arranges them into clusters. Also, the proposed SS-GSO method constructs a fitness function by including various sources of information, like total energy, residual energy, and luciferin value. Several simulation runs were executed to test how much better the SS-GSO approach worked. The comparison results showed that while evaluating clustering time, our proposed SS-GSO technique performs 22.91%, 50.03%, 42.42%, 58.06% better, in case of Total energy consumption 27.02%,14%,33.76%,41.97% more energy efficient, in Cluster lifetime 9.2%,19.88%,35.91%,40.54% less and in Packet delivery rate 8.29%,14.05%,17.67%,23.97% better as compared with other heuristic techniques, such as ACO, GWO, MFO and LEACH.

Co-digestion of cow manure and food waste for biogas enhancement and nutrients revival in bio-circular economy - Yasir Abbas; Sining Yun; Ayaz Mehmood; Fayyaz Ali Shah; Kaijun Wang; Elsayed Tag Eldin; Wahidah H. Al-Qahtani; Shafaqat Ali; Patrizia Bocchetta (Chemosphere, 2023)

The quest for negative electrode materials for Supercapacitors: 2D materials as a promising family - Muhammad Sufyan Javed; Abdul Mateen; Iftikhar Hussain; Salamat Ali; Sumreen Asim; Awais Ahmad; Elsayed tag Eldin; Majed A. Bajaber; Tayyaba Najam; Weihua Han (Chemical Engineering Journal, 2023)